Seasonal pattern of single falls and recurrent falls amongst community-dwelling older adults first applying for long-term care services in Hong Kong. (25th November 2019) - Qian, Xing Xing; Chau, Pui Hing; Kwan, Chi Wai; Lou, Vivian Wq; Leung, Angela Y M; Ho, Mandy; Fong, Daniel Y T; Chi, Iris
Abstract: Background: few studies had investigated seasonal pattern of recurrent falls. Objective: to examine seasonal pattern of both single and recurrent falls amongst community-dwelling older adults first applying for long-term care (LTC) services. Methods: a cohort of 89, 100 community-dwelling Hong Kong older adults aged 65 and over first applying for LTC services from 2005 to 2014 was obtained. Logistic regression models were used to examine seasonal pattern in single and recurrent falls, whilst controlling for gender, age and year. Results: amongst 89, 100 older adults, about 32% fell in past 90 days. Amongst the fallers, 34% fell recurrently. In 2014, the incidences of all fall, single fall and recurrent fall were 1.95, 0.80 and 1.15 per person-years, respectively. For single falls, the 90-day fall risk was highest during November to February with an odds ratio (OR) of 1.29 (95% confidence interval [CI] 1.19–1.41), compared with the lowest one during July to October. For recurrent falls, the highest OR for 90-day risk was highest during November to February (1.46, 95% CI 1.31–1.64) as well. Conclusions: single and recurrent falls both peaked during winter months. Interventions, such as implementing educational publicity and sending reminder to older adults in fall season, may be considered.